Race and gender moderation of the relationship between cessation beliefs and intentions: is race or gender message segmentation necessary in anti-smoking campaigns? - Parvanta, S. (Oxford University Press, 2013)
Debate persists over whether different message strategies in anti-smoking campaigns are needed for audiences of different races or genders. This study considers the need for ‘message segmentation’, which is the process of differentiating the beliefs that might be the focus of messages for population subgroups. We have two aims: (i) lay out an approach that yields evidence about the necessity for message segmentation and (ii) demonstrate and assess findings from this approach using the formative evaluation for the Philadelphia Anti-Smoking Campaign. We examine whether associations between beliefs about quitting smoking and intention to quit are moderated by race (black/white) or gender. Data came from a representative sample of 501 adult smokers (46% black; 56% female) surveyed in July 2010 for the campaign’s formative evaluation. Out of 26 beliefs about cessation, 8 were significantly related to cessation intention regardless of subgroup affiliation, suggesting that these would be promising beliefs for messages in a unified campaign. Four beliefs were significant for white smokers only, and three beliefs were significant for female smokers only. The evidence justified a unified message approach because subgroups shared enough beliefs that could become message strategies to increase cessation across smokers without the added costs associated with message segmentation.